Pengelolaan Terpadu Limbah Cair Ternak Kambing Desa Kompang Kecamatan Sinjai Tengah Kabupaten Sinjai Sulawesi Selatan - Azmi Mangalisu; Rahmawati Arma (Universitas Muhammadiyah Parepare)
Goat livestock business that is carried out by the community has the potential as a source of income, but it is still considered a sideline because agricultural business is still the main focus. The agricultural business undertaken is still dependent on chemical fertilizers which are fairly expensive steps in Kompang Village. In addition, public knowledge of the dangers of chemical fertilizers is very minimal or even practically nonexistent. Likewise, the knowledge of the utilization of goat waste in the form of feces or urine has not been utilized as sufficient organic fertilizer. Knowledge and pregnancy enhancement are carried out with counseling methods and training in processing goat waste in the form of goat urine. The activities carried out are the preparation stage in the form of a location survey, the distribution of questionnaires to see the initial knowledge of farmers/breeders, the provision of material or training on wastewater treatment, and the direct simulation of how to make organic liquid fertilizer. The preparation phase of tools and materials that will be needed in the process of making organic liquid fertilizer (POC). The next step is the procedure for making POC. The last stage is the harvesting of POC, packaging, and marketing of POC that has been produced. The output of this community service is the utilization of livestock waste in the form of goat urine as liquid organic fertilizer. Farmers and livestock enthusiastically participate in this activity so that their knowledge and understanding of integrated livestock waste management.